Pengaruh Reputasi Auditor dan Mekanisme Corporate Governance Terhadap Integritas Laporan (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2008-2010) - Fitri Damayanti; Rochmi Rochmi (Esensi: Jurnal Bisnis dan Manajemen, 2014)
This study aims to obtain empirical evidence about the effect of auditor reputation, corporate governance mechanism (independent commissioner managerial ownership, institutional ownership) to integrity  of financial statement at  the  manufacturer  companies  in  Indonesia.  Integrity  of  financial  statement define as how far a financial statement disclosure shows truth and honest information. Independent variables used in this study were reputation auditor and corporate governance  mechanism  was  analyzed  by  independent  commissioner managerial ownership, institutional ownership. Dependent variable used in this study is integrity of financial statement was analyzed by conservatism. Study’s  sample was  manufacturer  companies  listed  in  Indonesia  Stock Exchange (IDX) period among 2008-2010. Data was collected by purposive sampling  method.  Total  56  manufacturer  companies  were  taken  as  study’s sample. The method of analysis of this research used multiple regression. The   results   of   this   research   showed   that   reputation   auditor   and independent   commissioner   had   significant   effect   to   integrity   of   financial statement. Meanwhile, Institutional ownership and managerial ownership had not significant effect to integrity of financial statementDOI: 10.15408/ess.v4i3.2431